Sustainable energy: a review of formic acid electrochemical fuel cells - Rees, N; Compton, R (Springer-Verlag, 2011)
Of the many candidate fuels for low-temperature fuel cells, one of the most promising is formic acid. Although it has been investigated as such for nearly 50 years, rapid advances in recent times have begun to release the potential for formic acid fuel cells as high-performance, portable fuel cells with some products about to reach the market. In this review, we briefly summarise the recent advances in formic acid fuel cells.